Assessment of diabetes mellitus type 2 treatment costs in the Republic of Serbia - Biorac Nenad; Jakovljević Mihajlo B.; Stefanović Danka; Perović Saša; Janković Slobodan (Vojnosanitetski Pregled)
Background/Aim. High morbidity and mortality rates, chronic course of disease and numerous clinical complications, make diabetes mellitus (DM) type 2 bear significant financial burden for healthcare system of Serbia. The aim of this study was to compare true disease-related expenses measured in the random sample of patients originating from the Central Serbia in 2007 and national estimate of total expenses based on available evidence on antidiabetic drugs and insulins acquisition costs in the same fiscal year. Methods. The study design was prevalence-based, bottom-up cost of illness analysis. It was implemented on a randomized sample of 99 adults with confirmed diagnosis of DM type 2. During 2007 all direct (drug acquisition, medical services, medical devices usage) and indirect costs associated with their primary disease (premature death, impaired working ability, early retirement, absentism), were taken into account. Other approach was to calculate average national rate of antidiabetic drugs and insulin utilization and sales at the domestic market during the mentioned period of time. Taking into consideration available estimate from the Institute of Public Health of Serbia of 475 000 people with this disease at the national level, we were able to compare these data. Assuming that our sample was enough representative and that the structure of costs was approximately similar at the local and national level, we were able to calculate an estimate of total cost of the disease. All costs were expressed in Serbian official currency, dinar (CSD). Results. Values of costs measured per patient in our sample in a given year were for drug acquisition 20 352.45 CSD, medical services 24 338.26 CSD, medical devices 3 174.46 CSD and loss of productivity and absentism 5 547.78 CSD. There were 2 cases of early retirement due to the disease and no cases of dialysis treatment or premature death. A total number of sickness absence days of employed patients, was 1 025 and a total number of hospital treatment days was 360. A total amount of all costs was 53 412.96 CSD per patient per year. According to the National Medicines and Medical Devices Agency an overall value of oral antidiabetic drug sales for 2007 per patient was 1 835.32 CSD and for insulins and analogs 2 948.18 CSD. Conclusion. Comparing true size of national financial burden of DM type 2 with experiences of other authors, we can see that it is comparable with European OECD average. But, if the structure of expenses is taken into account, Serbia is more similar to those countries reported in the Third World economies. Our local findings on a sample of diabetic population show that real patient expenses were even 2.28 times higher than those estimated at the national level.